REDUKSI PASIR BESI PANTAI SIGANDU KABUPATEN BATANG MENJADI SPONGE IRON MENGGUNAKAN BURNER GAS ASETILIN - Itsnain Aji Pangestu; Sugeng Tirta Atmadja; Yusuf Umardhani (JURNAL TEKNIK MESIN, 2015)
In this experiment has been done laboratory scale processing of iron sand from Sigandu beach regency of Batang to be sponge iron by direct reduction using oxyacetylene gas burner at 1200 oC. Based on the experiments conducted through the process of making a composite pellets briquettes, and conducted trials combustion using oxyacetylene gas burner with the composition of the briquettes is 75% iron sand, wood charcoal is added as much as 20% functions as a reductant, and 5% tapioca which functions as glue. The iron sand into iron is required a long production stages, begins with the extraction or separation of magnetic minerals with non-magnetic using magnets to increase levels of Fe. From the results can be known content extraction iron sand of Sigandu beach is 62.27%. In the composition testing using AAS method (Atomic Absorption Spectrometry) iron sand composition (raw material) obtained 3.56% Si, 6.12% C, 1.42% Mg, and Fe 51.23%, after reduced to 62.13% Fe, 1.20% Mg, 0.85% C and 1.98% Si. From these data seen increase in the Fe content of 10.09%, accompanied with a decrease in content impurities in the sponge iron